Strategi Pengembangan Kerbau Rawa Di Kabupaten Hulu Sungai Utara Kalimantan Selatan - Ahmad Suhaimi; Rum Van Royensyah; Heldawati Heldawati (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2019)
This study aims to determine an alternative development strategy swamp buffalo in the region of Hulu Sungai Utara, South Borneo. This study uses survey method participation premises observation techniques, followed by analysis of the LFA (Logical Framework Approach). The results showed strategy development swamp buffalo in the Sapala Village Paminggir Districts namely increasing the use of appropriate technologies, held a contest races swamp buffalo, increase community participation skills, the role of extension workers and government, guidance / counseling from relevant agencies, increase capital, improve working relationships operation between businesses, farms made close to transport links, as well as improving land use with good breeding, and improve institutional performance.